The Relationship Between School Principals’ Leadership and Learning Innovation in The Implementation of The Merdeka Curriculum - Arfiani Yulianti Fiyul (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the relationship between school principals’ leadership and instructional innovation in the implementation of the Merdeka Curriculum. As this curriculum promotes the concept of learning freedom, school principals play a pivotal role in guiding and fostering innovation in teaching and learning. The research adopts a quantitative approach with a correlational design. Data were collected through questionnaires distributed to 150 school principals and teachers across various schools in Indonesia that have adopted the Merdeka Curriculum. The findings reveal a significant correlation between principals’ leadership and learning innovation, with transformational leadership emerging as a key contributor to the successful implementation of innovative teaching practices. The study offers practical implications for educational policy, particularly in reinforcing the strategic role of school leadership in advancing learning innovation in alignment with the principles of the Merdeka Curriculum.